Resolution of Budd‐Chiari syndrome secondary to needle foreign body migration in a dog: treatment with surgery and intravascular stenting. Issue 1 (30th January 2015) - Massie, Anna; Phillips, Heidi; Solomon, Jeffrey
Abstract : A 6.5‐year‐old, female spayed German short‐haired pointer dog was presented with a two‐week history of ascites. The dog was depressed with a severely distended abdomen. Peritoneal fluid analysis revealed a modified transudate. A metallic linear foreign body was identified cranial to the pyloric antrum by advanced imaging. A fibrous tract of tissue extending from the pyloric antrum to the hilar region of the right medial liver lobe was dissected surgically. The foreign body was removed by dissection of the fibrous tract, which relieved visible compression of the caudal vena cava and all hepatic veins. By three days postoperatively, ascites had not resolved and a caudal cavagram confirmed narrowing of the thoracic caudal vena cava at the diaphragm. Eight days postoperatively, a caudal vena caval stent was placed, relieving the pressure gradient across the narrowing and resulting in complete resolution of clinical signs.